(untitled) (Journal of Tourism and Hospitality Education, 2019)
The global economic development and changing perception of customers led to increasing amount of consumption in luxury products, yet the academic interest on luxury tourism shopping remained as limited. The aim of this manuscript is to fill the gap by taking the attention to the unused potential of luxury shopping in tourism market. The methodology of this study will be literature review related to the findings in the previous literature, and the critical evaluation of the findings. The research will begin with a brief introduction of luxury goods and the motivational factors for customers to engage in luxury shopping. Then, the focus will shift to the context of tourism, with current examples of luxury shopping tourism practices across the world such as in Dubai, Hong Kong and so forth. Finally, the study will conclude that the development of luxury shopping tourism in a particular destination can be facilitated through the contributions of governmental bodies to lure international brands to the region with necessary fiscal arrangements such as tax reductions, as well as local stakeholders to improve the conditions for luxury shopping tourism infrastructure including accommodation facilities, means of transportation, shopping malls, as well as development of new high quality brands for the consumption of both international and national tourists.